Effects of fixed-dose indapamide/perindopril combination on arterial function in patients with hypertension and chronic kidney disease: key results of the CAMERTON program - Zh. D. Kobalava; V. V. Kireeva; V. S. Chernomorets; E. A. Troitskaya; Yu. V. Stavtseva (Российский кардиологический журнал, 2019)
Aim. To study the effects of fixed-dose indapamide/perindopril combination on endothelial function and arterial stiffness in patients with uncontrolled stage 1-2 hypertension (HTN) and chronic kidney disease (CKD).Material and methods. Total of 100 patients with uncured or uncontrolled with ≥3 months antihypertensive therapy HTN and CKD G3 (67% females, mean age 59,1±12,5 years) were included in the study. Each patient took indapamide/perindop combination in accordance with 1 of 3 existing regimes (depending on doses) for 3 months. Primary aim was to assess the effects of indapamide/perindopril combination on endothelial function and parameters of arterial stiffness after 12 weeks of treatment (assessment by AngioScan diagnostic complex). Secondary aims were achievement of target blood pressure (BP) after 4 and 12 weeks of therapy and assessment of glomerular filtration rate (GFR) and the albumin-tocreatinine ratio (ACR) changes after 12 weeks.Results. Initially, there was an increase in arterial stiffness parameters in all patients, and during treatment decrease was observed: central systolic BP (SBP) from 120±10,1 to 112,9±6,3 mm Hg, median augmentation index from 10,9% to 4,6%, stiffness index from 8,1±2,4 to 7,1±0,9, vascular age decreased by 9,6% (р< 0,001 for trend). Significant improvement of endothelial function was observed regardless of diabetes presence: occlusion index increased from 1,5±0,3 to 1,7±0,5, median phase shift — from -4,6 to -2,4 ms (p< 0,01). After 4 weeks, 27% of patients reached target BP, by the end of the study — 90%. A decrease in the median ACR from 16,3 to 15,0 mg/g, GFR increase from 50,2±7,6 to 53,6±8,7 ml/min/1,73 m2 were observed (p< 0,01 for trend).Conclusion. Therapy with a fixed-dose indapamide/perindopril combination in patients with uncontrolled stage 1-2 HTN and G3 CKD leads to a significant improvement in arterial stiffness, endothelial and renal function, and achievement of target BP in 90% of patients.